Internship at “el recuerdo cdi” under the program my first steps from University of Córdoba (2020)
In this report will be explained and exposed every detail of my experience in this internship. This internship was to be carried out at “CDI El Recuerdo” in Montería, but due to health issues in the country it was not possible to complete the process personally. This report will be about the pedagogies used to design the materials and lessons, along with the challenges and difficulties I encountered during the process. This internship is offered by the University of Córdoba, and any student in last semester can apply for it. This internship is part of the project “my first steps”, and it is offered as graduation option. This project is part of a macro project that goes by the name of “Cordoba Transformada”, which was created by the University and it is carried out in “CDI El Recuerdo.” In this internship, one of my responsibilities was to create 4 lessons from a unit created by the team (my partners and advisor). However, the lessons were not carried out as expected because of the national health situation. Although it was not possible develop the whole process in the CDI, the responsibilities were assumed and fulfilled. This paper describes all the features that made part of the internship process and all that was used to support my work. It is divided into 6 sections: introduction, pedagogies, methodology, experience, conclusions and recommendations, and limitations. They will be developed along the document.